Single-cell mass cytometric analysis of peripheral immunity and multiplex plasma marker profiling of non-small cell lung cancer patients receiving PD-1 targeting immune checkpoint inhibitors in comparison with platinum-based chemotherapy - Neuperger, Patrícia; Szalontai, Klára; Gémes, Nikolett; Balog, József Á.; Tiszlavicz, László; Furák, József; Lázár, György; Puskás, László G.; Szebeni, Gábor J. (Frontiers in Immunology, 2023)
Introduction The effect of platinum-based chemotherapy (Chem.) and second- or multiple- line immune checkpoint PD-1 blocking therapy by Nivolumab or Pembrolizumab (ICI) was assayed in the peripheral blood of non-small cell lung cancer (NSCLC) patients. Methods Flow cytometry was used to detect NSCLC-related antigen binding IgG antibodies. The Luminex MagPix multiplex bead-based cytokine/chemokine detecting system was used to quantitatively measure 17 soluble markers in the plasma samples. Single-cell mass cytometry was applied for the immunophenotyping of peripheral leukocytes. Results The incubation of patient derived plasma with human NSCLC tumor cell lines, such as A549, H1975, and H1650, detected NSCLC-specific antibodies reaching a maximum of up to 32% reactive IgG-positive NSCLC cells. The following markers were detected in significantly higher concentration in the plasma of Chem. group versus healthy non-smoker and smoker controls: BTLA, CD27, CD28, CD40, CD80, CD86, GITRL, ICOS, LAG-3, PD-1, PD-L1, and TLR-2. The following markers were detected in significantly higher concentration in the plasma of ICI group versus healthy non-smoker and smoker controls: CD27, CD28, CD40, GITRL, LAG-3, PD-1, PD-L1, and TLR-2. We showed the induction of CD69 and IL-2R on CD4+ CD25+ T-cells upon chemotherapy; the exhaustion of one CD8+ T-cell population was detected by the loss of CD127 and a decrease in CD27. CD19+CD20+, CD79B+, or activated B-cell subtypes showed CD69 increase and downregulation of BTLA, CD27, and IL-2R in NSCLC patients following chemotherapy or ICI. Discussion Peripheral immunophenotype caused by chemotherapy or PD-1 blocking was shown in the context of advanced NSCLC.